MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIK SISWA SMK MELALUI PEMBELAJARAN SOFTWARE CABRI 3D - Alpha Galih Adirakasiwi (Department of Mathematics Education, Universitas Kuningan, 2016)
This research purpose of this article is to know the increase of the ability of mathematical communicationÂ based on the learning software cabri on 3D material. Research method used is quasi experiment with group design control post. The experimental units is two classes which use learning with software cabri 3D, and conventional learning. The subject of this research is thirty students class XI SMK in Karawang. Instrument used to measure mathematical communication ability is written test in explanation form. The result of data analysis shows that learning with using software cabri 3D gave influence to the increasing of mathematical communication ability on three dimension material. The average score of control group is 20,73, and the average score of treatment group is 24,97